(untitled) (Jurnal Teknodik, 2024)
This study aims to analyze the comparative performance of three AI platforms (ChatGPT, Gemini, and Perplexity) as learning media for Accounting 1, based on the Sub-CPMK outlined in the Semester Learning Plan (RPS). The research employs a Qualitative Comparative Analysis (QCA) method, evaluating platform responses using six criteria: accuracy, clarity, coherence, engagement, scalability, and informativeness. The results reveal that ChatGPT scored the highest (96%), followed by Gemini (92%) and Perplexity (91%). ChatGPT excels in clarity, engagement, and informativeness; Gemini shows strength in scalability, while Perplexity performs consistently in accuracy and coherence. This study highlights the importance of adaptive and collaborative AI utilization in Accounting 1 learning to enhance educational quality while ensuring ethical and secure usage.